A Comparative Analysis of Morphometry and Morphology of Otamiri Watershed, South-eastern Nigeria - Temple Probyne Abali; Ibiso Michael Inko-Tariah; Dickson Kinikanwo Nsiegbe; Lucky Baripara Nkii; Oye Ideki (Zien Journals, 2021)
A comparative analysis of Morphometry and Morphology of the watershed was examined with the aid of GIS and fieldwork respectively. The catchment is mostly covered by dwindling rainforest vegetation due to intensive anthropogenic activities such as urbanization, farming, sand mining, dredging etc. The study entailed an evaluation of streamflow characteristic of the basin by the delineation of the watershed and determination of morphometric parameters such as the linear, aerial and relief aspects. The focus on Drainage Density (Dd), Stream Frequency (Fs), Bifurcation Ratio (Rb), Stream Order (Nu), Stream Length (Lu), Texture Ratio (T), Elongation Ratio (Re), Circulatory Ratio (Rc), Form Factor (Rf) etc. The result showed that the drainage network is dendritic type, indicating textural homogeneity and requiring less structural controls as well as variation in bifurcation ratio from 2.00 to 5.50. Elongation ratio of 7.00 depicts a basin of elongated shaped category. The stream order ranges from first to sixth order basin. The basin was found to possess low drainage density, drainage texture and stream frequency which indicates highly permeable soils and low relief. Other investigated parameters include low overland flow revealed recharge related measures, surface water augmentation measures that can be undertaken for water resource management as well as soil conservation structures in the study area. Furthermore, the results of fieldwork analyses using the regression and correlation analysis showed that there is a high positive correlation between channel morphology and discharge as well as urbanization index, infiltration capacity showed a negative relationship with channel morphology, but a positive correlation with discharge which is the potent factor that determines channel morphology. Furthermore, sediment yield had a relatively low correlation coefficient that is not statistically significant with channel morphology. Consequently, it can be concluded that urbanization and discharge are the most significant factors that determine the present channel shape and size characteristics of Otamiri river channel.
Keywords: Urbanization; watershed; morphology; morphometry